Use and appropriation of ICT in the educational practices of teachers of the program of environmental engineering of the Universidad Francisco de Paula Santander. (November 2018) - Meza, M; García, C
Abstract: The academic evidence from developing countries shows the change that universities are making in the production of knowledge and the influence they exert on the development of their countries, given the integration of ICT in academic activities, which has made it possible to improve production processes and the exchange of knowledge through the network. The objective of the research was to characterize the use and appropriation of ICTs, which the teachers of the environmental engineering program of the UFPSO, do in their pedagogical practices, through a descriptive methodology with a quantitative and qualitative approach, which allowed to use instruments the collection as surveys, focus group and personal interview, to analyze the results through the statistical software SPSS and Atlas Ti. From the results of the work it is concluded that most teachers consider ICT as a resource to improve the teaching-learning process, where at the beginning they are used as a tool for the transmission of information, and that as they appropriate, they allow the construction of knowledge.